Die Verzeitlichung der Bildung: Selbstbestimmung im technisch-medialen Wandel - Leineweber, Christian (transcript, 2020)
Looking at the temporalisation of education, Christian Leineweber addresses the constitutive dependence of subjective self-determination on time.